Examining the drivers of ecological footprint components: is pursuing food security environmentally costly for Nigeria? - Obekpa, H. O.; Alola, A. A.; Adejo, A. M.; Echebiri, C. (Elsevier, 2025)
Amidst the fact that Nigeria’s ecological footprint exceeds its biocapacity by 58 percent, rapid population increase, and incessant farmers and herders conflict continue to pose a significant danger to the country’s food security drive. Motivated by this observation, this study attempts to examine whether the pursuit of food security agenda amidst population increase, and economic growth exhibits a significant impact on the country’s aggregate ecological footprint and footprints of built-up land, carbon, cropland, fishing grounds, forest products, and grazing land especially over the period 1981–2020. While the quantile regression method provides robustness to the main Kernel-based regularized least square approach, the Kernel-based regularized least square approach found that food production activities and geometric increase in food production, i.e., the square of food production, both increase the aggregate ecological footprint and footprints of built-up land, cropland, forest products. This revelation suggests serious environmental woe arising from the country’s attempt to improve food production. While the aggregate ecological footprint and its components, except for the fishing ground, experience a surge with an increase in population, economic growth promotes carbon, cropland, fishing ground, and grazing land footprints. The result of the investigation provides insight and measures for improving food security without necessarily increasing ecological pressure. The study suggests that policy measures that directly target recycling, preservation, and conservation of agricultural activities and products be encouraged to reduce the demand on the ecological components.